Treatment of squamous cell carcinoma of the mobile tongue or tongue margins: an interdisciplinary challenge - Hauswald, Henrik; Zwicker, Felix; Rochet, Nathalie; Jensen, Alexandra; Debus, Jürgen; Lindel, Katja (Acta oncologica, 2013)
Background. Standard treatment is surgery with stage dependent postoperative radio(chemo)therapy, however, for organ preservation preoperative radio(chemo)therapy is used as an individual approach. The present analysis was performed to access outcome and toxicity of radiotherapeutical treatment of squamous cell carcinoma of the tongue. Patients and methods. Sixty-six patients (median age 55 years) with cancer of the mobile tongue (nϭ30) or tongue margins (nϭ36) treated between 1982 and 2006 were retrospectively analyzed. Treatment consisted of deﬁnitive- (nϭ13, median dose 66 Gy), adjuvant- (nϭ31, median dose 60 Gy) or neoadjuvant radiotherapy (nϭ22, median dose 40 Gy) and chemotherapy (nϭ34) or immunotherapy (nϭ1). Results. After a median follow-up of 29 months the three- and ﬁve-year overall survival (OS) rates were 59% and 46%, respectively. The median OS was 54 months. Forty-two patients achieved complete remission whereas 14 patients showed partial remission. The one- and two-year loco-regional progression-free survival (LRPFS) rates were 76% and 58%, respectively. The median LRPFS time was 36 months. In χ2-test, T-stage showed a trend towards impact on local recurrence (Pearson, pϭ0.082). In multivariate analysis, alcohol consumption (pϭ0.003) and gender (pϭ0.031) were prognostic. Grade III/IV acute toxicity was seen in 52% of patients. None of the locally controlled patients reported grade IV or higher late toxicity. Conclusion. No statistically signiﬁcant differences between treatment modalities were found, but one should keep in mind that organ preservation plays a major role for quality of life. None of the locally controlled patients reported grade IV or higher late toxicity. However, tumor recurrence is common, especially in advanced tumor stage. Interdisciplinary concepts, further increasing the chance of tumor control are warranted.